Production of AlN/CNT reinforced PVA nanofibers as a thermal conductive net for thermal interface applications - Avcioglu, Suna; Ozcan, Muecahid; Kaya, Cengiz; Kaya, Figen; Cevik, Sinem (ELSEVIER, 2024)
The amount of heat generated by electronic components is increasing daily, in line with their growing power and performance. Consequently, there is a heightened demand for thermal interface materials for enhanced cooling of electronics. This study employs a novel approach to fabricate a nano composite thermal interface material on copper substrates to address this challenge. The thermal interface coatings, consisting of carbon nanotubes (CNT) and aluminum nitride (AlN)-reinforced polyvinyl alcohol (PVA) nanofibers with and without an epoxy resin matrix, are fabricated using the electrospinning technique. The findings demonstrate the successful fabrication of a 2.5 mu m-thick CNT/AlN-PVA nanocomposite fiber mat coating with an average fiber diameter of 318 nm onto copper substrates. Scanning electron microscope (SEM) images revealed that the AlN particles and CNTs penetrated the fibers. The successful incorporation of AlN particles into PVA fibers was also verified by the Fouriertransform infrared spectroscopy (FT-IR) spectrum of CNT/AlN-PVA nanofibers. No major weight loss was observed in the thermogravimetric (TG) analysis curves up to 200 degrees C, indicating the thermal stability of coatings. The thermal diffusivity of the copper substrate coated with the CNT/AlN-PVA nanocomposite fiber mat was measured at 36.6 mm 2 /s. Moreover, the developed CNT/AlN-PVA nanocomposite fiber mat was also applied on top of the fire-retardant epoxy resin-coated copper substrate, which is conventionally used in electronic devices to provide electrical insulation. SEM images revealed that the existence of an epoxy layer on top of copper substrates did not alter the fiber formation during the electrospinning process, and an approximately 2.5 mu mthick CNT/AlN-PVA nanofiber mat was effectively embedded in the epoxy layer after a 1-hour electrospinning process. The thermal diffusivity of the resulting epoxy matrix CNT/AlN-PVA nanofiber reinforced nanocomposite coating is determined to be 7.792 mm 2 /s, which is 30-fold higher compared to the thermal diffusivity of neat epoxy resin coatings (0.254 mm 2 /s).
Keywords: Aluminum nitride; Carbon nanotube; Epoxy resin; Thermal conductivity; Chemistry